Identification of runs of homozygosity in Western honey bees (Apis mellifera) using whole‐genome sequencing data. Issue 1 (17th January 2023) - Gmel, Annik Imogen; Guichard, Matthieu; Dainat, Benjamin; Williams, Geoffrey Rhys; Eynard, Sonia; Vignal, Alain; Servin, Bertrand; Neuditschko, Markus
Abstract: Runs of homozygosity (ROH) are continuous homozygous segments that arise through the transmission of haplotypes that are identical by descent. The length and distribution of ROH segments provide insights into the genetic diversity of populations and can be associated with selection signatures. Here, we analyzed reconstructed whole‐genome queen genotypes, from a pool‐seq data experiment including 265 Western honeybee colonies from Apis mellifera mellifera and Apis mellifera carnica . Integrating individual ROH patterns and admixture levels in a dynamic population network visualization allowed us to ascertain major differences between the two subspecies. Within A. m. mellifera, we identified well‐defined substructures according to the genetic origin of the queens. Despite the current applied conservation efforts, we pinpointed 79 admixed queens. Genomic inbreeding ( F ROH ) strongly varied within and between the identified subpopulations. Conserved A. m. mellifera from Switzerland had the highest mean F ROH (3.39%), while queens originating from a conservation area in France, which were also highly admixed, showed significantly lower F ROH (0.45%). The majority of A. m. carnica queens were also highly admixed, except 12 purebred queens with a mean F ROH of 2.33%. Within the breed‐specific ROH islands, we identified 14 coding genes for A. m. mellifera and five for A. m. carnica, respectively. Local adaption of A. m. mellifera could be suggested by the identification of genes involved in the response to ultraviolet light ( Crh‐BP, Uvop ) and body size ( Hex70a, Hex70b ), while the A. m. carnica specific genes Cpr3 and Cpr4 are most likely associated with the lighter striping pattern, a morphological phenotype expected in this subspecies. We demonstrated that queen genotypes derived from pooled workers are useful tool to unravel the population dynamics in A. mellifera and provide fundamental information to conserve native honey bees. Abstract : Past genetic diversity analyses in honey bees especially focused on drone genomes, as their haploid nature facilitated cost‐efficient whole‐genome sequencing. To substantially improve the quality of population structure analyses in honey bees we have used reconstructed queen genotypes from pooled workers to identify runs of homozygosity (ROH) in 265 Western honey bee colonies, including two subspecies namely Apis mellifera mellifera and Apis mellifera carnica . We integrated individual ROH patterns and admixture levels in a high‐resolution population network visualization, which allowed us to ascertain major differences between the two subspecies.